Single crystal growth and vortex matter phase diagram in HgBa2CuO4+x superconductor - Stamopoulos, D.; Pissas, M. (JOURNAL OF MATERIALS PROCESSING TECHNOLOGY, 2001)
In this work we report on the crystal growth process, the crystal structure and the phase diagram of HgBa2CuO4+chi high T-e superconductor. Precise global DC magnetization measurements, using a SQUID magnetometer, have been performed, on two single crystals in magnetic fields parallel to the c-axis (H \ \ c) with T-c = 95 and 89.9 K, respectively. The irreversibility curve H-irr(T) decreases exponentially up to a temperature T* and after it changes slope abruptly. The magnetization curves at a fixed temperature as a function of magnetic field show two peaks, namely H-fp(T) and H-sp(T). (C) 2001 Elsevier Science B.V. All rights reserved.